Analysis of printed circuit heat exchanger (PCHE) potential in exhaust waste heat recovery. (5th March 2022) - Zhang, Hongfei; Shi, Lingfeng; Xuan, Wang; Chen, Tianyu; Li, Yurong; Tian, Hua; Shu, Gequn
Highlights: A design concept of printed circuit heat exchanger is proposed. A printed circuit heat exchanger is designed and manufactured. The feasibility and thermal-hydraulic performance are investigated. Four different structures are simulated for optimization. Abstract: Exhaust waste heat recovery technology based on power cycles requires high efficiency, low flow resistance, and a compact structure for exhaust gas heat exchangers. It is a huge challenge for traditional heat exchangers, such as double tube or shell and tube heat exchangers. A printed circuit heat exchanger (PCHE), which is a compact heat exchanger, has not been used in the heat exchange process between the exhaust gas and supercritical CO2 . Focusing on this application, a novel design concept of PCHE based on a comprehensive performance index is proposed, which fully considers the differences in physical properties and working conditions between the exhaust gas side and the CO2 side. A series of experiments were carried out in a CO2 -based transcritical power cycle system. The experimental test results show that the PCHE with a novel structure is stable and feasible. To further optimise the PCHE, a numerical analysis of different structures was conducted. The calculation results show that the comprehensive performance of the PCHE with an optimised structure was improved by 11.92%. This research shows that PCHE has great potential for achieving a compact design with excellent performance, especially for use in engine waste heat recovery.